Solid Dosage Forms with Fixed-Dose Combinations of Active Pharmaceutical Ingredients: Therapeutic Importance and Review of Formulation Strategies - Maksimović, Nevena; Đuriš, Jelena (Archives of Pharmacy, 2026)
Fixed-dose combination (FDC) products contain at least two active pharmaceutical ingredients (APIs) in a single dosage form. Monolithic, multilayer, and multiparticulate formulations are widely employed in the manufacture of solid fixed-dose combination products, such as tablets and capsules. Among the technologies used in production, active film coating, compression coating and liquid dispensing technology are the most widely employed, with increasing attention being given to 3D printing of FDC products. Selecting the appropriate formulation strategy for the development of these drugs is crucial to minimising their disadvantages. Clinically, they offer improved efficacy, safety, and tolerability in the treatment of conditions such as hypertension, type 2 diabetes, tuberculosis, pain, various infections, hormonal disorders and contraception. From the patient’s perspective, they provide practicality and simplify therapy by reducing pill burden, which leads to greater adherence and, consequently, improved therapeutic outcomes and quality of life.